Continuous rotary membrane emulsification for the production of sustainable Pickering emulsions. (15th February 2022) - Ekanem, Ekanem E.; Wilson, Amy; Scott, Janet L.; Edler, Karen J.; Mattia, Davide
Graphical abstract: Highlights: Continuous rotary membrane emulsification for generation of monodisperse emulsions. The system includes a stainless-steel tubular membrane and a 3-D printed flow cell. Continuous phase flowrate effectively decoupled from shear generation. New approach to increase productivity of continuous membrane emulsification. Abstract: A continuous rotary membrane emulsification (cRME) system, allowing the decoupling of droplet generation from continuous phase (CP) flowrate, is presented here for the first time. The decoupling results in higher productivity and greater control compared to traditional crossflow and rotational membrane emulsification processes. A design of experiment (DoE) investigated the influence on droplet formation of CP flow, membrane rotational speed and emulsion composition, using a Pickering emulsion consisting of 1 wt% keratin solution and varying concentrations of oxidised cellulose nanofibrils. Experiments showed that CP flowrate had a negligible effect on droplet diameters in a wide range (between 78 and 241 µm), with uniformity index as low as 0.14 for optimal membrane rotational speeds and different oxidised cellulose nanofibrils (OCNF) concentration. cRME has the potential to overcome low emulsion concentration limitations of continuous membrane emulsification systems, paving the way to significantly increase the productivity and application in personal care, food and drugs industries.